Actividad antioxidante, contenido de fenoles totales y antocianinas en jugo de tres variedades de granada (Punica granatum L.) - Fuentes Dávila, Rober Gerson (2023)
The pomegranate (Punica granatum L.) is a fruit that contains various bioactive compounds, however the composition of the pomegranate juice is strongly influenced by the variety, the extraction method, the state of maturation, as well as the storage conditions. That is why the main goal of this research was to determine antioxidant capacity, total phenols content and anthocyanins of pomegranate juice in three pomegranate varieties: Mollar de Elche, Wonderful and Mollar Valenciana. In the quantification of the antioxidant capacity, the DPPH method was used in which values of 88.56 ± 0.99, 93.10 ± 0.13 and 52.82 ± 0.10% were found, expressed in inhibition percentage of DPPH, for the varieties Mollar de Elche, Wonderful and Mollar Valenciana respectively. For the quantification of phenolic compounds, the Folin-Ciocalteu method was used, in which values of 762.01 ± 10.18, 828.36 ± 16.43 and 463.62 ± 6.77 mg AGE / 100 mL were found for the varieties Mollar de Elche, Wonderful and Mollar Valenciana respectively. . For the quantification of the anthocyanins content, the differential pH method was used in which values of 8.14 ± 0.36, 32.83 ± 2.10 and 3.19 ± 0.02 mg cyanidin 3-glucoside/ 100mL were found for the varieties Mollar de Elche, Wonderful and Mollar Valenciana respectively.